(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Urinary bladder transitional cell carcinoma is serious cancer that affects both men and women. It is a heterogeneous neoplasm with varying biological behavior, with most cases being early non-invasive with a proclivity for recurrence and some cases progressing to invasive tumors. The tumor stage and histological grade, which are employed as predictive indicators for the tumor and play a critical role in therapy, are key for clinicopathological aspects. The repeatability was low because of the subjectivity of histological grading. Many studies have shown the importance of quantitative tumor analysis in assessing tumor recurrence and muscular invasion, while others have shown the utility of nuclear measurement as a prognostic tool for bladder cancer. This study compares the benefits of nuclear image analysis as a method for evaluating transitional cell carcinoma of the urinary bladder to subjective standard histological grading.